Dialogic and Generative Reflection: An Application of the Critical Appreciative Process in Program Evaluation - Ye He; Tiffany L. Smith; Malitsitso Moteane (Journal of MultiDisciplinary Evaluation)
Background: Even though the positive potential of reflective practice is widely acknowledged across professional fields, it has been recognized that reflective practice may be carried out primarily as an individual-based exercise, and at the technical or descriptive level without generative impact. Dialogic reflective processes involving both evaluators and program directors are far from being systematically implemented or examined.